SIZE DISTRIBUTION OF AEROSOLS AT BARROW IN ALASKA : A CASE STUDY IN SPRING - ザイゼン, ユウジ; オカダ, キクオ; イケガミ, ミワコ; アオキ, テルオ; サワ, ヨウスケ; ニシオ, フミヒコ; タチバナ, ヨシヒロ; ZAIZEN, Yuji; OKADA, Kikuo; IKEGAMI, Miwako; AOKI, Teruo; SAWA, Yousuke; et al. (National Institute of Polar Research, 1998)
P(論文) Concentration, size distribution and morphological features of aerosol particles were observed at Barrow in Alaska during the period 13-28 April 1997 together with concentrations of gaseous species (SO_2,NO and NO_2). The concentrations of gaseous species were less than 50 pptv except for locally polluted air. Aerosol size distributions suggested the occurrence of new particle formation from the gas phase in spite of very low concentrations of gaseous species, especially in the air mass from lower latitudes during the latter part of the observational period. In the air mass from higher latitudes, new particle formation was assumed to be not active. The largest maximum was found at 0.1-0.2μm radius in most of the observation periods, suggesting that the size distributions have been influenced by wellaged particles. The dominant component of aerosol particles in this size range is considered to be sulfate-containing particles. Another maximum was found occasionally at 0.02-0.05μm radius. This kind of air mass was possibly influenced by air from lower latitudes. departmental bulletin paper